“I can live a normal life”: Exploring adherence to antiretroviral therapy in Indonesian adolescents living with HIV - Nuraidah Nuraidah; Dessie Wanda; Happy Hayati; Imami Nur Rachmawati; Agung Waluyo (Belitung Nursing Journal, 2022)
Background: Adherence to antiretroviral therapy (ART) can be challenging since it needs to be continued for a lifetime. At their age, adolescents start to be responsible for their life, and this continued therapy might be a challenge for them. Objective: This study explored the experiences of adherence to ART in adolescents living with HIV in Jakarta, Indonesia. Methods: A qualitative study with an Appreciative Inquiry (AI) approach was employed to explore challenges adolescents face in ART adherence which focused more on positive aspects of the experience. In-depth interviews were conducted with ten adolescents who were selected purposively based on criteria including those aged 13-19 years, having been diagnosed with HIV infection and receiving ART for more than a year, and never having discontinued ART. All participants were registered in the outpatient clinic in one top referral hospital in Jakarta. The data were analyzed using thematic analysis. Results: Five themes were identified from the data: living a normal life, wanting to be healthy, taking medication on time, challenges in undergoing treatment, and there is hope. Conclusion: Adolescents with HIV want to live as normal and healthy as possible, like other adolescents. Even though adolescents face several challenges to comply with ART, they try to take the medication as prescribed. The findings of this study serve as input for nurses to maintain compliance with ARVs in adolescents who have HIV.